Peningkatkan Penguasaan Kosakata Bahasa Inggris Pada Siswa Sekolah Menengah Kejuruan Dengan Menggunakan Media Pembelajaran Teka Teki Silang - Nasrullah Nasrullah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to determine the increasing students’ vocabulary mastery in vocational school by using Crossword Puzzle Learning Media. Based on the results of field observations, it was found that vocabulary is a problem that has not yet found a solution. Based on these results, we also need to examine the existing problems more deeply. This research method uses a quantitative approach. This quantitative approach is used to increase the Students’ Vocabulary Mastery in Vocational School Students using Crossword Puzzle Learning Media. This research also uses a descriptive approach to describe the situation that occurred. The results of the data collected through questionnaires after the learning process was completed, of the 85 students Respondence who were the objects of this research, it was found that There are 15% or 13 students answered that they really liked it. There were 50% 42 students answered Like 17% or 14 students answered normal. There were 8% or 7 students who answered that they did not like it and 10% or 9 students answered that they really did not like English subjects using crossword puzzles. The second finding is the level of students' memorization abilities. There are 28% or 24 students who answered very well. There were 45% or 30 students who answered well. There are 15% or 13 students who answered moderately. There are 12% or 10 students who are less able to memorize and there are 10% or 8 students who answer cannot memorize. It can be concluded that Crossword Puzzle Learning Media made it easier for students to memorize English Vocabulary. This is also shown by the increased enthusiasm of students in participating in lessons in class.